Chrysin Modulates Aberrant Epigenetic Variations and Hampers Migratory Behavior of Human Cervical (HeLa) Cells - Raina, Ritu; Almutary, Abdulmajeed G.; Bagabir, Sali Abubaker; Afroze, Nazia; Fagoonee, Sharmila; Haque, Shafiul; Hussain, Arif (Frontiers in Genetics, 2022)
Purpose: Plant derived phytochemicals have shown epigenetic modulatory effect in different cancers by reversing the pattern of DNA methylation and chromatin modulation thereby restoring the function of silenced tumor suppressor genes. In the present study attempts have been made to explore chrysin mediated epigenetic alterations in HeLa cells. Methods: Colony formation and migration assays followed by methylation specific PCR for examining the methylation status of CpG promoters of various tumor suppressor genes (TSGs) and the expression of these TSGs at transcript and protein level were performed. Further, global DNA methylation, biochemical activities of DNA methyltransferases (DNMT), histone methyl transferases (HMT), HDAC (histone deacetylases) and histone acetyl transferases (HAT) along with the expression analysis of chromatin modifying enzymes and H3 and H4 histone modification marks analysis were performed after chrysin treatment. Results: The experimental analyses revealed that chrysin treatment encourage cytostatic behavior as well as inhibit the migration capacity of HeLa cells in a time and dose dependent manner. Chrysin reduces the methylation of various tumor suppressor genes leading to their reactivation at mRNA and protein levels. The expression levels of various chromatin modifying enzymes viz DNMTs, HMT, HDACs and HATS were found to be decreased and H3 and H4 histone modification marks were modulated too. Also, reduced global DNA methylation was observed following the treatment of chrysin. Conclusion: This study concludes that chrysin can be used as a potential epigenetic modifier for cancer treatment and warrants for further experimental validation.